Valorization of horticultural agro-residues and marine for sustainable poultry nutrition: a response surface methodology-based approach with argan press cake and anchovy bone residues - Boumendil, Ilham; Taaifi, Yassine; Yassif, Fatima-Zahra; Tesse, Rajaa; Boutaleb, Nadia; Safi, Amal (Comunicata Scientiae, 2025)
Although rich in proteins and minerals, the salty by-products of anchovy processing, especially bones, are usually discarded because of their high sodium chloride (NaCl) content. This study developed a process to desalt anchovy bone residues and combine them with rinsed argan press cake, an agro-industrial co-product used in animal feed, to formulate a functional poultry diet. Simple solid–liquid extraction with tap water (1:1, m/v) reduced NaCl from 15.4% to 4.7%. A Response Surface Methodology (RSM) then evaluated mixtures of desalted bones (10–90%) and rinsed argan press cake (10–30%). Nutritional parameters measured included NaCl, calcium, phosphorus, ash and total nitrogenous matter. The optimal diet, with 10% desalted bones and 10% press cake, achieved a final NaCl content of 0.49% while maintaining essential nutrients. These findings demonstrate the feasibility of integrating marine and agro-industrial co-products into sustainable poultry feed, supporting circular economy principles